(untitled) (International Seminar on Syariah and Law (INSLA), 2020)
Land represents one of the key resources of wealth for a country with economic, social and environmental dimension. Inevitably, security of land tenure and dealings is vital in managing land resources as a trust from the Almighty to humankind. In view of this, Islam considers protection of property and wealth as one of the five fundamentals of shariah or the maqasid as-shariah. Similarly, the significance of secure land tenure for sustainable development has been acknowledged by the United Nations. This paper seeks to examine the advantages of safeguarding land tenure to the economic and social well-being as well as repercussions from failure to uphold the same particularly in facing the pandemic of covid-19. The research employs doctrinal approach. The findings of this paper suggest that the government has to play proactive role in ensuring land tenure and dealings are guaranteed and protected by enhancing the legislative framework of land administration system in Malaysia.